PEMBELAJARAN DIFERENSIASI MATEMATIKA BERBASIS TEKNOLOGI - Baharuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat STKIP Citra Bakti, 2026)
The development of digital technology has brought about significant changes in educational practices, particularly in mathematics learning, which increasingly demands an adaptive and personalized approach. This study aims to review technology-based differentiated mathematics learning, focusing on its effectiveness, challenges, and contribution to improving learning quality. This study, based on relevant literature review, collected articles and research from 2020 to 2025, demonstrates that technology-based differentiated mathematics learning consistently improves mathematics learning outcomes, student motivation, and participation. Technologies such as GeoGebra, Desmos, and adaptive learning platforms enable teachers to tailor content, processes, and learning products to individual student needs. However, the effectiveness of implementation is highly dependent on teacher readiness and infrastructure availability. Key challenges identified include limited teacher digital competency, disparities in technology access across regions, and the lack of long-term research assessing the sustainability of this model. This study contributes to integrating theoretical perspectives with modern technology-based mathematics learning practices. Thus, the results of this study provide a conceptual and empirical basis for the development of an inclusive, adaptive, and sustainable mathematics learning model in the digital era.